환경단체의 조직-공중관계성이 조직이미지와 시민들의 기부후원의도에 미치는 영향 연구 - 주경일(Kyung-Il Joo) (한국비교정부학보, 2019)
This study attempted a statistical verification on how organization-public relationship of Korea Federation for Environmental Movements influence on the organizational image and intention for donation and support. The study result showed that the trust and communal relationship among organization-public relationship influenced on both organizational image and intention for donation and support. Also, commitment had significant influence on organizational image while satisfaction had significant influence on the intention for donation and support. This study verified the influence of organization-public relationship on the non-profit organization and contributed on opening the new horizon for researches on the organization-public relationship. The study results showed that it is necessary to improve trust to promote donation and support. Thus, the environmental organizations should open monthly income and spending in detail and enhance the financial transparency through auditing. However, this study only reflected the recognition of citizens instead of mutual recognition between the organization and the public. Since this study is limited in exploring the complete organization-public relationship, there should be further researches to enhance the value of general theory for organization-public relationship theory. KCI Citation Count: 0